Pleas for patience from the cumulative future self. (26th April 2021) - Maglio, Sam J.; Hershfield, Hal E.
Abstract: Current selves wield all the power in intertemporal tradeoffs. Although one set of future selves will make similar tradeoffs in the future, another self – who we term the cumulative future self – falls on the receiving end of those dictated decisions. How current selves commune with the cumulative future self determines whether the former heed pleas, from the latter, for patience.